Growth and Yield Dynamics of Rainfed Rice Fields by Providing Municipal Solid Waste Compost - Aisar Novita; Fitra Syawal Harahap; Zuriani Ritonga; Vitri Renny Triyanti; Merlyn Mariana (UNIVERSITY OF LAMPUNG, 2024)
The rice productivity in Panai Tengah was still relatively low, producing 4.75 Mg ha-1, compared to the national production of 5 to 6 Mg ha-1. Low rice productivity was caused by limiting factors in land use, namely, physical and biological factors, soil chemistry, and agricultural systems. Providing organic fertilizer or municipal waste compost is one way to overcome the constraints on the soil’s physical, biological, and chemical characteristics. This study aims to determine the response to the growth and yield of rainfed rice fields in Kecamatan Panai Tengah with a dose of Municipal Solid Waste Compost (MSWC). This research was conducted by taking soil samples in the rainfed rice fields and then analyzing them in the experimental field at the Faculty of Science and Technology, Labuhanbatu University. The analysis stage was for six months, from seeding to harvesting. The methodology for this study was a non-factorial randomized block design consisting of 7 treatments. The result showed that applying MSWC at a dose of 18 Mg ha-1 showed high yields. The recommendation to farmers was to give 18 Mg ha-1 of MSWC to increase the yields of their rice fields.